Re-placing regionalisms: Atlantic Canada in 21st century narratives - Smith, Will (2007)
Though traditionally mapped as a margin, Stephen Henighan has argued that 'By the late 1990s it seemed that only writers from Atlantic Canada - Wayne Johnston, Alistair MacLeod, David Adams Richards - still wrote Canadian novels; this may help explain the surge in these writers popularity.' This duality of being Canadian and exploring a regional social identity, in context with an evolving global community, is navigated by contemporary Atlantic Canadian film and literature alike. Contemporary narratives challenge both stereotypes and cultural marginalisation by constructing 'authentic' representations of place, without recourse to overt commodification. The strategies developed in negotiating past ideas of regional identity constitute a contemporary regional imaginary. Contemporary narratives conjure a fluid idea of regional experience, open to multiple identity claims and forces of globalisation.